2006
DOI: 10.1115/1.2748830
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rising and Falling K Profiles on SCC Growth Rates in High-Temperature Water

Abstract: Effects of rising and falling stress intensity factor (K) profiles on the stress corrosion cracking (SCC) growth rates of stainless steel and nickel alloys has been studied in high-temperature water. Sophisticated test control software was used that changes loading (P) based on crack length (a) to achieve a specific K trajectory by controlling dK∕da, not simply dP∕dt. The majority of SCC problems develop adjacent to welds, which have a complex residual stress profile versus wall thickness. This, coupled with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Thus, there is an inherent synergy between crack advance and growth rate itself (or dK/da as the crack advances). The data presented by Andresen and Morra [47] indicate that when changes in K are controlled by dK/da, very different responses can be seen for rising vs. falling K conditions. For example, rising K results in an increased growth rate, which causes faster increase in K, which is a positive feedback.…”
Section: Rising K or Dk/da Effectsmentioning
confidence: 89%
See 2 more Smart Citations
“…Thus, there is an inherent synergy between crack advance and growth rate itself (or dK/da as the crack advances). The data presented by Andresen and Morra [47] indicate that when changes in K are controlled by dK/da, very different responses can be seen for rising vs. falling K conditions. For example, rising K results in an increased growth rate, which causes faster increase in K, which is a positive feedback.…”
Section: Rising K or Dk/da Effectsmentioning
confidence: 89%
“…Initially, when the crack depth is small, K could increase very rapidly because it is proportional to the square root of crack depth (Kar p a). Studies on austenitic SSs and Ni alloys in high-purity water with 2000 ppb O 2 at 288°C have shown that rising K (+dK/da) at K values that are relevant for LWR components can increase the CGRs significantly, whereas decreasing K (ÀdK/da) has little or no effect [47]. Under rising K conditions, growth rates can be more than two orders of magnitude higher than those under constant K conditions.…”
Section: Rising K or Dk/da Effectsmentioning
confidence: 97%
See 1 more Smart Citation
“…The effects of dissolved oxygen concentration or electrochemical potential on oxidation kinetics and crack growth behaviour of stainless steels in high temperature water environments have been investigated. [10][11][12][13][17][18][19][22][23][24][25][26] CGRs of sensitised 304SS and solution annealed non-sensitised stainless steels increased monotonically with electrochemical potential, which tended to reach a plateau at high DO concentrations where corrosion potential and CGR were not sensitive to DO in this range. Decreasing electrode potential moderately inhibited crack growth of prior hardened austenitic stainless steels in high temperature pure water, which was less significant than that of sensitised 304 stainless steels and as solution annealed low C stainless steels in similar environments.…”
Section: Effects Of Do Concentration On Scc Growth Ratesmentioning
confidence: 94%
“…6,22,23,[27][28][29][30] The change of bulk DO concentration could affect the 7 SCC growth rates versus DO for 316NG weld metals: a specimen HTW2 and b specimen WOW1 in 288uC pure water a specimen HTW4 with high ferrite content; b specimen WOW3 with low ferrite content 8 Crack growth kinetics monitored by ACPD measurements for 316NG weld metals with different ferrite contents concentration gradient of oxygen between the crack mouth and the crack tip thus could affect the crack tip water chemistry and the resultant crack growth. 6,22,23 It is assumed that the controlling mechanism for SCC in 2 ppm DO water would not be different from that in 7 or 11 ppm DO water, leading to the point of view that the change of crack tip oxidation kinetics would be the primary cause for the change of SCC growth rates as the result of changing DO in water. The actual processes would be complicated due to the interaction of crack tip oxidation kinetics and mechanics involved in SCC element processes.…”
Section: Effects Of Do Concentration On Scc Growth Ratesmentioning
confidence: 99%